Formação continuada para professores de Educação Infantil: concepções de profissionais da rede municipal de ensino de Fortaleza. - Guedes, Elizangela Amaral (2011)
Research and innovative actions have pointed to the importance of investment in professional development of teachers felt that the democratization of education involves the training of these professionals, and contribute to their recovery and improvements in their working conditions. The focus of this work is related to the ongoing training of teachers for kindergarten, which is necessary as a demarcation that educational policies aimed at teacher training are quite large. For these professionals, discussions about the gaps in initial and continuing education can be considered as specific cases, since what is observed is that training for the teachers who work in groups of children aged zero to five years in many cases do not address the specific issues of education of these children, leading to mistakes in their teaching. The research sought to examine the concepts of continuing education and continuing education of perception experienced in the period 2005 to 2010 a group of professionals made up of technical education and teachers who work in Early Childhood Education of the municipal school of Fortaleza, Ceará. The theoretical brings the concepts of continuous training of teachers in the general framework, based on the ideas of Antonio Nóvoa (1997, 1999) and Gimeno Sacristan (1995). For the specific case of the continuous training of teachers working in kindergarten, the ideas of Julia Oliveira-Formosinho (2001a, 2009), were taken as theoretical support throughout this study. The approach to work is the qualitative character, and the strategy used the case study. To collect data were semi-structured interviews with seven technical education, three teachers and six nursery pre-school teachers. The analysis of the collected material showed that the concepts of continuous training of technical education are related to upgrading and expansion of knowledge and conceptions of the teachers emphasized the need for change in pedagogical practice. With respect to perceptions of the impact on teaching practices of teachers, education techniques highlighted mainly the changing conceptions of children by the teachers and they, in turn, highlight the opportunities to exchange experiences with colleagues and reflect about their practices through the theory / practice relationship.